The Anglo-Saxon Critical Geopolitics and Its Critics. A Theoretical Debate that Contributes to the Analysis in World Politics - Estenssoro, Fernando; Orellana, José (Instituto de Estudios Avanzados - Universidad de Santiago de Chile, 2021)
This is a theoretical article that exposes the meaning and the main proposals of the so-called critical geopolitics, as well as which are the main criticisms that have arisen from classical and neo-classical geopolitics. In this sense, it is pointed out that the critical geopolitics proposal, made by a group of Anglo-Saxon political geographers, has resulted in an important stimulus to the epistemological debate in Political Geography, as well as in other disciplines that study world politics, such as Political Science and International Relations, among others. This debate has occurred, mainly (although not only) in the Anglo-Saxon academy, being less developed and known in the Latin American academy. Likewise, this debate is contextualized in the historical development of political geography as an academic discipline.